Leveraging electronic word-of-mouth to enhance mobile app consumer satisfaction: the mediating role of brand awareness - Hua, Xiangzhou; Mohd Hasan, Nurul Ain; De Costa, Feroz (Success Culture Press, 2024)
This study aimed to examine the influence of electronic word-of-mouth (Ewom) on consumer satisfaction with mobile apps, and the mediating role of brand awareness. Data was collected through a questionnaire of 494 WeChat users in China. The results showed volume, valence, and source of Ewom significantly predicted consumer satisfaction. Furthermore, brand awareness mediated the relationship between Ewom and satisfaction. The findings suggest businesses should actively manage Ewom and focus on improving brand awareness and trust to enhance customer satisfaction with their mobile apps. Specific measures are proposed such as prompt response to Ewom and brand building through social media engagement.